Epidemiology of criniviruses: an emerging problem in world agriculture - Tzanetakis, Ioannis E.; Martin, Robert R.; Wintermantel, William (Frontiers in Microbiology, 2013)
The genus Crinivirus includes the whitefly-transmitted members of the family Closteroviridae. Whitefly-transmitted viruses have emerged as a major problem for world agriculture and are responsible for diseases that lead to losses measured in the billions of dollars annually. Criniviruses emerged as a major agricultural threat at the end of the twentieth century with the establishment and naturalization of their whitefly vectors, members of the genera Trialeurodes and Bemisia, in temperate climates around the globe. Several criniviruses cause significant diseases in single infections whereas others remain asymptomatic and only cause disease when found in mixed infections with other viruses. Characterization of the majority of criniviruses has been done in the last twenty years and this article provides a detailed review on the epidemiology of this important group of viruses.